Atlas of Infections in Neurosurgery and Spinal Surgery - Akhaddar, Ali (Springer International Publishing : Imprint: Springer, 2017)
This Atlas is the first reference Atlas covering exclusively all aspects of this multifaceted topic. It is designed to serve as a succinct appropriate resource for neurosurgeons, spinal surgeons, radiologists, neurologists, microbiologists, researchers and infectious disease specialists with an interest in cranio-cerebral and vertebro-medullary infections especially encountered in neurosurgery and spinal surgery. This Atlas is designed to deliver more information in less space than traditional texts, allowing for quick review of the essential facts of this complex infectious topic through pictures. Pertinent imaging and laboratory information are combined with intraoperative photographs and illustrations to help readers visualize variable presentations and enhance their perioperative management. The comprehensive content of this richly-illustrated book covers different infectious diseases seen on neurosurgical and spinal practices. The Atlas is divided into five sections, after a general introduction, the second section focuses on infections of the brain and its coverings. The third section focuses on vertebromedullary infections. The fourth section includes infections following cranial and spinal surgery, and the fifth section provides a description of the most important specific pathogens and other particular conditions. The format makes it easily accessible and includes a definition of each infection and its epidemiology, main clinical presentations, imaging features and laboratory findings, treatment options, and prognosis information. It will help the reader in choosing the most appropriate way to manage this multipart problem. In addition, the book supplies clinicians and investigators with both basic and more sophisticated information and procedures relating to the complications associated with neurosurgical and spinal infections.
Keywords: Medicine.; Neuroradiology.; Infectious diseases.; Neurology.; Neurosurgery.; elektronické knihy; electronic books